Setia Berbuah Petaka (Ihwal Kutuk Astabasu dan Lahirnya Bhisma dalam Cerita Adiparwa) - I Nyoman Duana Sutika (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2018)
The story in which the curse of Astabasu and the birth of Bhisma are narrated is one of the stories in Adiparwa. It is narrated that BagawanWasistha condemned Astabasu (eight basus) for stealing Nandini, his cow. Prabhata, one of the Astabasus, stole the cow for Dyoh, his wife whom he loved so much and who wanted to consume the milk produced by the cow. Astabasu and Goddess Gangga were condemned for the mistake they had made. Goddess Gangga did not mind reducing the curse of Astabasu for which they were supposed to return to where they had come from, the heaven. When the first seven basus were born, they were returned to where they had come from by Goddess Gangga by throwing them away. Bhisma, the reincarnation of the eighth basu was more heavily and longer punished as he had been primarily responsible for the theft. During his life, Bhisma entirely served the Kuru family and strongly promised that he would never be married ‘brahmacari’ to make his parents happy.